Decreased antioxidant-related superoxide dismutase 1 expression in peripheral immune cells indicates early ethanol exposure - Kado, Akira; Moriya, Kyoji; Inoue, Yukiko; Yanagimoto, Shintaro; Tsutsumi, Takeya; Koike, Kazuhiko; Fujishiro, Mitsuhiro (Scientific reports, 2024)
Alcohol consumption increases oxidative stress and imbalances in the antioxidant system, even with ethanol (EtOH) exposure at a young age. This study assessed changes in the antioxidant system following young EtOH exposure in peripheral immunity and measured sensitive indicators of heavy alcohol consumption. We used peripheral blood mononuclear cells (PBMCs) from 197 male university students without smoking habits to examine changes in antioxidant-related gene expression in vitro and in PBMCs. In vitro, the antioxidant system was impaired by EtOH. Next, we examined the expression of 84 antioxidant-related genes in the PBMCs of 162 young adults, among which the superoxide dismutase (SOD) 1 expression was most negatively correlated with alcohol consumption degree. The plasma SOD1 level had the highest area under the curve value (0.806) for heavy alcohol consumption. Our data demonstrated that a decreased SOD1 level is a sensitive indicator of an impaired antioxidant system and heavy alcohol consumption with early EtOH exposure.